Effect of Bed Temperature and Extruded Height on 3D Printed PLA Mechanical Properties - Mohd Hisam, Muhamad Faris; Mohd Azham Azmi (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Additive manufacturing or commonly known as 3D printing is rapidly developed and widely used throughout the world. 3D printing technology is increasingly being used for mass modification and manufacture in agriculture, healthcare, automotive, and aviation industries. PLA is the most common plastic filament material used in 3D printing due to its biodegradability and ease of use. PLA has low melting point, strong strength, minimal thermal expansion, good layer adhesion, and high heat resistance when annealed. The mechanical properties of 3D printed Polylactic Acid (PLA) are influenced by various printing parameters including bed temperature and layer height. This parameter gave a big impact to the mechanical properties and qualities of the fabricated components. PLA was printed with different bed temperature which is 80°C, 90°C, and 100°C, while the layer height at 0.12mm, 0.16mm, and 0.20mm for each bed temperature. The impact of this parameter shown by the research conducted to fabricate the 3D specimens using Fused Deposition Modelling machine and analysis the properties through tensile and flexural testing to get the tensile and flexural strength. The tensile and flexural strength improves with layer thickness and bed temperature. Smaller layer height improved surface quality and finer detail that can enhance interlayer bonding that leads to increase the tensile strength. Increase in heat dissipation from one layer to another layer which leads the post heating of layer which are already bonded and improve the strength. Layer height 0.12mm with 80°C have the best tensile strength and modulus of elasticity while the best flexural strength is the specimen printed at temperature 100°C with 0.16mm layer height.